Making the business process outsourcing decision: why distance matters. Issue 9 (5th September 2016) - Gerbl, Martina; McIvor, Ronan; Humphreys, Paul
Abstract : Purpose: The purpose of this paper is to develop a framework that incorporates both firm- and process-level factors for understanding location distance choice in the business process outsourcing (BPO) decision. Design/methodology/approach: The research involved undertaking in-depth case study analysis of a number of BPO decisions in six German companies, and employing transaction cost economics (TCE) and the resource-based view (RBV) as a theoretical basis. Findings: The findings have shown that existing literature in the operations management (OM) literature does not provide a complete understanding of the complexities of location distance choice in the BPO decision. This decision requires an understanding of a range of factors at both the firm- and process-level. The findings here enhance the understanding of how these factors interact to influence the potential distance options. Practical implications: The findings have shown how organisations can influence the factors that affect the location distance choice including modularising business processes, developing outsourcing capabilities, and supplementing internal skills in areas such as cultural management and performance monitoring. Originality/value: This is one of the first studies in the OM field to analyse how organisations make the decision in relation to local, nearshore, and offshore location distance options. The paper has highlighted the importance of OM concepts such as performance management and continuous improvement to this phenomenon, and the paper has offered a number of important areas for further research.